Frailty Severity Impacts Development of Hospital-acquired Conditions in Patients Undergoing Corrective Surgery for Adult Spinal Deformity. Issue 7 (14th August 2021) - Pierce, Katherine E.; Kapadia, Bhaveen H.; Bortz, Cole; Alas, Haddy; Brown, Avery E.; Diebo, Bassel G.; Raman, Tina; Jain, Deeptee; Lebovic, Jordan; Passias, Peter G.
Abstract : Study Design: This was a retrospective cohort study of a national dataset. Purpose: The purpose of this study was to consider the influence of frailty on the development of hospital-acquired conditions (HACs) in adult spinal deformity (ASD). Summary of Background Data: HACs frequently include reasonably preventable complications. Eleven events are identified as HACs by the Affordable Care Act. In the surgical ASD population, factors leading to HACs are important to identify to optimize health care. Methods: Patients 18 years and older undergoing corrective surgery for ASD identified in the American College of Surgeons' National Surgical Quality Improvement Program (ACS-NSQIP). The relationship between HACs and frailty as defined by the NSQIP modified 5-factor frailty index (mFI-5) were assessed using χ 2 and independent sample t tests. The mFI-5 is assessed on a scale 0–1 [not frail (NF): <0.3, mildly frail (MF): 0.3–0.5, and severely frail (SF): > 0.5]. Binary logistic regression measured the relationship between frailty throughout HACs. Results: A total of 9143 ASD patients (59.1 y, 56% female, 29.3 kg/m 2 ) were identified. Overall, 37.6% of procedures involved decompression and 100% fusion. Overall, 6.5% developed at least 1 HAC, the most common was urinary tract infection (2.62%), followed by venous thromboembolism (2.10%) and surgical site infection (1.88%). According to categorical mFI-5 frailty, 82.1% of patients were NF, 16% MF, and 1.9% SF. Invasiveness increased with mFI-5 severity groups but was not significant (NF: 3.98, MF: 4.14, SF: 4.45, P >0.05). Regression analysis of established factors including sex [odds ratio (OR): 1.22; 1.02–146; P =0.030], diabetes mellitus (OR: 0.70; 0.52–0.95; P =0.020), total operative time (OR: 1.01; 1.00–1.01; P <0.001), body mass index (OR: 1.02; 1.01–1.03; P =0.008), and frailty (OR: 8.44; 4.13–17.26; P <0.001), as significant predictors of HACs. Overall, increased categorical frailty severity individually predicted increased total length of stay (OR: 1.023; 1.015–1.030; P <0.001) and number of complications (OR: 1.201; 1.047–1.379; P =0.009). Conclusions: For patients undergoing correction surgery for ASD, the incidence of HACs increased with worsening frailty score. Such findings suggest the importance of medical optimization before surgery for ASD.